Test results on direct containment heating by high-pressure melt ejection into the Surtsey vessel: The TDS test series - Allen, M. D.; Blanchat, T. K.; Pilch, M. M. (Sandia National Laboratories, 1994)
The Technology Development and Scoping (TDS) test series was conducted to test and develop instrumentation and procedures for performing steam-driven, high-pressure melt ejection (HPME) experiments at the Surtsey Test Facility to investigate direct containment heating (DCH). Seven experiments, designated TDS-1 through TDS-7, were performed in this test series. These experiments were conducted using similar initial conditions; the primary variable was the initial pressure in the Surtsey vessel. All experiments in this test series were performed with a steam driving gas pressure of {approx_equal} 4 MPa, 80 kg of lumina/iron/chromium thermite melt simulant, an initial hole diameter of 4.8 cm (which ablated to a final hole diameter of {approx_equal} 6 cm), and a 1/10th linear scale model of the Surry reactor cavity. The Surtsey vessel was purged with argon (<0.25 mol% Osub 2) to limit the recombination of hydrogen and oxygen, and gas grab samples were taken to measure the amount of hydrogen produced.